The efficacy of single-dose albendazole for the treatment of ascariasis - Deddy S Putra; W Dalimunthe; M Lubis; S Pasaribu; Chairuddin Lubis (Paediatrica Indonesiana, 2005)
Objective This study aims to assess the efficacy of single-dosealbendazole in treating mild, moderate, and severe ascariasis.Methods Stool specimens were collected from randomly selectedelementary school children in Suka village, Sumatera Utara, fromMarch to April 2002. Based on the number of eggs per gram feces(NEPG), samples were categorized as mild (NEPG < 7000), mod-erate (NEPG 7000-35,000), or severe (NEPG > 35,000) ascari-asis. All subjects then received 400 mg albendazole orally. NEPGcount was repeated on the 7 th , 14 th , 21 st and 28 th day after treat-ment. The chi-square test was used to compare cure rates be-tween subjects with mild, moderate, and severe ascariasis. TheANOVA and Kruskal-Wallis tests were employed to analyze quan-titative data.Results From the 134 specimens collected, we found mild ascari-asis in 57 (42.5%), moderate ascariasis in 57 (42.5%), and severeascariasis in 20 (15%). There was no significant difference be-tween the three groups in NEPG after treatment (P>0.05). Thecure rate and egg reduction rate on day 28 after treatment was 100%.Conclusion A single dose of 400 mg albendazole is effective forthe treatment of mild, moderate, and severe ascariasis.